Tycoon aide / Nur Aina Aqilah Abdullah … [et al.] - Abdullah, Nur Aina Aqilah; Mokhtar, Irfan Fawwaz; Roslan, Nur Farah Izzati; Amir, Muhamad; Mohd Ali, Zaqwan (Division of Research and Industry Linkages, 2017)
Our application focuses on helping new businesses or existing businesses that would want to establish their production abroad. In other words, the application will be advising the new businessman and businesswoman on their direction of their business. We will have features and criteria for the Businessman/Businesswoman to excel and will be having points for every criteria that they are good at. By using this application, they would be given the suitable ways to penetrate the markets abroad based on their capabilities and criteria. This could help them to have a greater chance to succeed in penetrating the new markets.